'It's a good thing we're doing, we just need to be better at it'. Forensic intellectual disability nursing experiences of Transforming Care: A multi‐perspectival interpretive phenomenological analysis. Issue 4 (11th January 2021) - Hudson, Nicholas; House, Richard; Robson, Neil; Rayner‐Smith, Kelly
Abstract: Background: Concerns have been expressed regarding the impact of Transforming Care (TC) an English deinstitutionalisation mandate, on forensic services. With nursing staff positioned as significant in delivering TC; this research explored nursing experiences. Method: Nine face‐to‐face semi‐structured interviews were completed with nursing staff working in either inpatient or community forensic teams. Multi‐perspectival interpretive phenomenological analysis was used to explore participants' experiences. Interviews were analysed independently, prior to a mini meta‐synthesis. Results: Participants from the inpatient group experienced TC as a threat, which resulted in consistency of perspective and practice. Participants from the community group viewed TC as a worthwhile challenge, which presented opportunity. The community infrastructure was experienced as inadequate by both groups, with the needs of people in forensic services needing more consideration, leading to widespread frustration. Conclusions: The blanket approach of TC may not be suitable for this population, with those leading TC perceived as naïve.